(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The objective of this work is to investigate the competencies of the mediator in matters of intestate succession, being that for this it is important to analyze the laws through the analogical method in relation to the actions of the mediators, as well as through the exegetical method and the documentary research technique, based on different authors in matters of family mediation and family business, being such of help to form a clearer idea regarding the actions, rights and duties that a mediator must comply with in matters of succession.